Physics-based guided wave structural health monitoring, and its integration in asset management modelling - Wu, Wen (2024)
Structural health monitoring (SHM) plays a vital role in ensuring the integrity of engineering infrastructures. Its primary objective is the implementation of a systematic approach to detect and identify potential damage or structural issues within these assets. By incorporating the identified information about asset condition from a monitoring system, engineers can utilise asset management models to manage maintenance activities in order to lower operating and maintenance costs and increase the life of these assets. The main aim of this thesis is to develop efficient damage identification methods using ultrasonic guided waves and integrate them with asset management modelling approaches.